Haemoglobin polymorphism and resistance to helminths in Red Sokoto goats - Buvanendran, V.; Sooriyamoorthy, T; Ogunsusi, R.A.; Adu, I.F. (Springer, 1981)
Haemoglobin variants were studied in a population of 104 Red Sokoto goats of over 1 year of age and in 49 kids. Three haemoglobin variants and 5 phenotypes were detected. The observed proportions of haemoglobin phenotypes in animals over 1 year of age differed from the expected numbers calculated on the basis of genetic equilibrium, while in kids there was good agreement between observed and expected values. There were significant differences in helminth egg counts among haemoglobin phenotypes. The heterozygotes had significantly lower egg counts than homozygotes. It is postulated that the discrepancy in the observed ratios of haemoglobin phenotypes of the older group was probably due to the differential susceptibility to helminth infection.